New Approaches in Interpreting the Quran in Contemporary Indonesia - Izza Rohman (Studia Islamika, 2007)
This study wants to look at Indonesian Muslim thought in relation to the interpretation of the Qur'ary especially its methodological issues. This topic is well-worth exploring also because it has been an increasingly prominent theme in contemporary debates on Islamic reform. It is in attempts to define the purpose and methods of Islamic reform and its legitimate boundaries that the debate concerning the Qur'an (primarily its interpretive approaches) between many contemporary Muslim thinkers comes into plays This study might be regarded as an effort to show how Indonesian Muslims have sought to participate in the debate, or to be more precise to incorporate some Indonesian Muslims' views into that debate. In doing so, this study limits its scope to the discussions in the Indonesian context during the past 20 years. It is within this period that lively discussions on interpretive approaches to the Qur'an have taken place in Indonesia.DOI: 10.15408/sdi.v14i2.544